MODELING AND VACCINATION STRATEGIES IN HANDLING COVID-19 IN INDONESIA - Rizziq, Faisal
COVID-19 is an infectious disease that has never been experienced before, therefore this disease is widespread and has become a global pandemic. In Indonesia, the number of cases of COVID-19 infection continues to increase every day. The proportion of vaccinations is one of the treatments for the COVID-19 pandemic, including in Indonesia. The implementation of vaccination must be considered because of limited resources. In order to study the development of COVID-19 cases and optimize the effect of vaccination on a population, it is necessary to study how to model the number of COVID-19 cases and also the proportion of vaccinations that must be given. In this study, we will discuss how to model the number of COVID-19 cases with the SIR model and optimize the proportion of vaccinations so that the number of cases in the future can be reduced optimally. The model used in this study is the Susceptible, Infection and Revovered model by adding a vaccination proportion factor. The simulation results show that the model can describe trends from COVID-19 data, and the implementation of vaccination can affect the number of cases of COVID-19 infection in the future. So that the implementation of optimum control in cases of COVID-19 infection can be considered in determining policies..